Effect of Pre-treatment Education Programs on the Anxiety of Patients Receiving Radiotherapy: An Integrative Literature Review - Fatemeh Heshmati Nabavi; Atefe Behboudifar; Zohre Pouresmail; Mohammad Naser Shafiee (Mashhad University of Medical Sciences, 2016)
Background: Stress and anxiety in cancer patients are caused by disease diagnosis, unfamiliar experiences, and therapy-related problems. In addition to the short duration of radiotherapy, receiving and understanding of the information about this treatment could be difficult for patients due to anxiety, fatigue, and mental pressure. Training of cancer patients about radiotherapy via educational programs could reduce pre-treatment anxiety. Aim: This systematic review aimed to integrate the information regarding the effects of pre-treatment educational training on the level of anxiety and distress symptoms of cancer patients receiving RT. Method: This systematic review was conducted to identify the studies comparing different methods of pre-treatment patient education before radiotherapy via searching in databases such as MEDLINE, PsycINFO, Web of Science, ClinicalKey, ProQuest, and PubMed. Selected studies included clinical reports on the effects of educational interventions on the anxiety of patients receiving radiotherapy. Excluded samples were commentaries and studies without intervention. Results: In total, we reviewed eight articles assessing the effect of educational interventions before radiotherapy on the anxiety of cancer patients. Educational interventions used in these studies included face-to-face consultation with a radiotherapist, group instructions with routine individual training using visual materials (e.g., brochures, booklets, videotapes, and PowerPoint presentations), group discussions, electronic instructions, written materials, and phone contact with a nurse. Implications for Practice: According our findings, pre-treatment education could reduce the anxiety of cancer patients before radiotherapy. These educational programs could be performed using written, visual, electronic, or face-to-face instructions. However, considering the condition of cancer patients and their treatment, selection of the appropriate training method requires further investigation through comparing different approaches.